Which Institutional Conscience? Awkward, Arbitrary, or Arrogant? - Fleck, Leonard Michael (American Journal of Bioethics, 2026)
The article critically examines the concept of secular institutional conscience in healthcare, particularly in hospitals, as proposed by Wasserman et al., who argue that secular institutions can possess a conscience similar to religious ones. It highlights concerns about the practical and ethical implications of allowing institutions to refuse family demands for life-prolonging care based on institutional conscience, especially amid contested definitions of death and medical futility. The discussion emphasizes that appeals to institutional conscience may shift conflicts from bedside decisions to administrative levels without resolving underlying disagreements rooted in value pluralism and trust. The article also questions the legitimacy and consistency of endorsing multiple institutional consciences across diverse healthcare settings, suggesting that such a framework could complicate rather than clarify ethical decision-making in patient care.